ENERGY AND ENVIRONMENTAL IMPACT ASSESSMENT OF ANDONI LGA, RIV-ERS STATE, NIGERIA - UGBANA NTE, FELIX (International Journal of Multidisciplinary Research and Studies, 2019)
Energy drives the economy of the world but its exploitation could have far-reaching impact. The focus of the study is Andoni Local Government environmental database and its oil and gas exploitation impact. The name Andoni is derived from the great river “Okwan Obolo” which the Ijaw toponym describes as “Idoni Toru”, the Portuguese call the same river Rio ‘Desan Domingos’ while the Dutch call it “river Loitombia”. The vegetation of the area is equatorial forest, followed by a mangrove transition zone and the beach sand secondary vegetation at the coast and back swamps. Key among the biodiversity are the elephants, sea turtles, python, and hippopotami by Niger Delta Environmental Survey. The average rainfall is 4035 ± 200MM annually. The Tidal range is 1.83m at springtime, but 0.76m at neap tide. The average temperature is 27± 5˚C and 80± 20 as relative humidity from the dry season to the rainy season. The geology is indicative of fluviolagonal deposit. The wind speed is 5-15m/s depending on the seasons. The average exposure rate from radiation (ʯRh-1) is 15.53 ± 2.15 as against the world average of 13.0. The absorbed dose rate is 135.1 ± 5.14 as against 60.0 world average. The energy potential is 96 oil wells from 7 multinational firms, which makes the Obolo study area significant.